2004
DOI: 10.1111/j.1525-1497.2004.30218.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a peer review process for web-based curricula

Abstract: The World Wide Web creates new challenges and opportunities for medical educators. Prominent among these are the lack of consistent standards by which to evaluate web-based educational tools. We present the instrument that was used to review web-based innovations in medical education submissions to the 2003 Society of General Internal Medicine (SGIM) national meeting, and discuss the process used by the SGIM web-based clinical curriculum interest group to develop the instrument. The 5 highest-ranked submission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…They suggested that academically qualified people must actively participate in development and training to improve e-learning. Four articles advised readers to allocate time to accurately budget and plan for the expected costs [ 23 , 41 , 44 , 48 ]. Budgets and policy statements should reflect commitment to the program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that academically qualified people must actively participate in development and training to improve e-learning. Four articles advised readers to allocate time to accurately budget and plan for the expected costs [ 23 , 41 , 44 , 48 ]. Budgets and policy statements should reflect commitment to the program.…”
Section: Resultsmentioning
confidence: 99%
“… Most ( n = 14) articles discussing software design focused on ready access to the e-learning platform. Access should be fast, easy to find, and always available; the platform should have a short loading time, and should provide reliable online access to all external links [ 7 , 36 - 40 , 45 , 46 , 48 , 49 , 52 , 53 , 70 ]. A secure connection is also important to support the privacy and legal requirements, copyright rules, and intellectual property issues [ 23 , 39 , 44 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process has built up a community of practice and best practices, and potential solutions have been identified among those facing similar challenges. 18 Rural teaching sites are being developed that must be given greater priority in terms of resources and teaching capacity, in partnership with provincial and local government. Schools in rural areas appear to provide some solutions.…”
Section: Implications Of the Projectmentioning
confidence: 99%
“…Thomas and Kern 29 provide an annotated bibliography of Internet resources, a search of which has become an essential early step in curriculum development, in addition to a search of the published literature. The resources section of the journal also includes Knight et al’s 30 difficult to classify article that describes the instrument used to rate Internet curricula for the last national SGIM meeting and that also includes a summary of the top five rated curricula. The instrument is an important innovation in development; the Internet curricula are resources for clinician‐educators.…”
mentioning
confidence: 99%